2021
DOI: 10.1101/2021.01.05.21249131
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ivermectin shows clinical benefits in mild to moderate COVID19: A randomised controlled double blind dose response study in Lagos

Abstract: IntroductionIn vitro studies have shown the efficacy of Ivermectin (IV) to inhibit the SARS - CoV-2 viral replication, but questions remained as to In-vivo applications. We set out to explore the efficacy and safety of Ivermectin in persons infected with COVID19.MethodsWe conducted a translational proof of concept (PoC) randomized, double blind placebo controlled, dose response, parallel group study of IV efficacy in RT - PCR proven COVID 19 positive patients. 62 patients were randomized to 3 treatment groups.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 28 publications
3
21
0
1
Order By: Relevance
“…A risk-of-bias summary graph is given in Figure 2 . Eleven studies 23 , 24 , 44 , 47 , 105 , 106 – 111 used satisfactory random sequence generation and allocation concealment. Two trials described satisfactory sequence generation, but it was unclear whether allocation was concealed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A risk-of-bias summary graph is given in Figure 2 . Eleven studies 23 , 24 , 44 , 47 , 105 , 106 – 111 used satisfactory random sequence generation and allocation concealment. Two trials described satisfactory sequence generation, but it was unclear whether allocation was concealed.…”
Section: Resultsmentioning
confidence: 99%
“…Ten trials reported adequate blinding of the participants/personnel and/or the outcome assessors. 23 , 24 , 44 , 105 , 107 , 109 , 110 , 111 , 113 , 114 The others were either unclear or high risk for blinding. We considered blinding to be a less important criterion for evaluation of evidence related to the review's primary outcomes, namely death and laboratory-confirmed COVID-19 infection, which are objective outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first randomized, double-blind, placebo-controlled, peer-reviewed study for publication in which the efficacy of ivermectin in preventing hospitalizations was evaluated [25][26][27]. In a meta-analysis that included 629 patients from 4 studies comparing ivermectin with placebo, it was observed as a secondary outcome that ivermectin was associated with clinical improvement in patients.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, ivermectin was also subjected to RT-PCR proven COVID-19 affected patient in two different doses comprised of 6 and 12 mg in every 84 h pattern for two weeks and compared with control (lopinavir/ritonavir daily for 2 weeks) group. In this trial, mean days to negative were respectively 6.0, 4.65, and 9.15 days which demonstrated the candidacy of Ivermectin 12 mg in the clinical management of COVID-19 infection ( Babalola et al, 2021 ). Besides, another clinical trial conducted on 600 participants showed significant abetment in RT-PCR conversion days along with mortality rate.…”
Section: Introductionmentioning
confidence: 63%